Schistosomal cryoglobulinemia associated with vasculitis and glomerulonephritis Case report - Mohamed M NasrAllah (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Schistosomiasis is an endemic, widespread disease in the subtropics and is a major cause of morbidity in developing countries. This is a report of a patient with a high titer of cryoglobulins composed of monoclonal IgM and anti-schistosoma IgG adult worm antibodies. This was associated with vasculitis and membranoproliferative glomerulonephritis. Improvement was noted after treatment with steroids and cyclophosphamide. This case presents 3 novel findings: first, it is the first documentation, that we could trace, of a clear link between schistosomiasis and type II “essential” mixed cryoglobulinemia in humans where anti-schostosomal antibodies form the IgG component of the cryoglobulins. Second,  it reports vasculitis associated with the shcistosomal cryoglobulins and finally it is a uniquel report of shcistosomal glomerulopathy responsive to immune suppression.